PMO-158 RS12979860 CC genotype is associated with baseline high numbers of CD56bright NK-cells, low numbers of CD3-CD56-CD16+ cells, low IL-10 HCV-specific production in CH-C therapy responders. (28th May 2012) - Carey, I; Bruce, M J; Joshi, D; Vergani, D; Agarwal, K
Abstract : Introduction: IL28B gene single nucleotide polymorphisms (SNPs) rs12979860 and rs8099917 help to predict treatment response in chronic hepatitis C (CH-C). Strong immune responses control HCV infection. Little is known on the association between IL28B SNPs, innate/adaptive immune responses in relation to Peg-IFN/ribavirin sustained virologic response (SVR) in CH-C. Aims: To evaluate the relationship between rs12979860 and rs8099917, pre-treatment frequency/phenotype of natural killer (NK) cells (innate immunity), HCV-specific immune responses (adaptive immunity), and SVR. Patients: 35 CH-C genotype 1 patients (23 males, median age 37 years) treated with Peg-IFN/ribavirin were divided in two groups: 18 responders (SVR), 17 non-SVR (nine non-responders and eight relapsers). Methods: rs12979860 and rs8099917 were tested by direct sequencing. Baseline numbers of NK cells (CD3 − CD56 + ), their subsets CD56 dim /CD56 bright, CD3 − CD56 ± CD16 ±, and expression of NK cells activation/inhibition (NKG2D/NKG2A) markers were investigated by flowcytometry on peripheral blood mononuclear cells (PBMC). PBMC IFN-γ/IL-10 production after exposure to HCV antigens was evaluated by intracellular cytokine staining. Results are presented as medians. Results: Rs12979860 genotype CC was more frequent in SVR than non-SVR (85% vs 15%), while non-CC genotypes (CT/TT) were present in 32% SVR vs 68% non-SVR. 75% SVR had TT genotype for rs 8099917 vs 25% non-SVR and non-TT genotypes (GT/GG) were more frequent in non-SVR then SVR (80% vs 20%, all pbright subset was higher in SVR than non-SVR (6.4% vs 2.9%, p=0.03). CD3 − CD56 − CD16 + cells subset was more frequent in non-SVR than SVR (11.4% vs 8.6%, p=0.05). The proportion of CD56 dim+ /NKG2D + cells was higher in SVR than non-SVR (47.1% vs 36.3%, p=0.04). While number of CD4+ HCV core-specific IFN-γ producing cells was similar in all groups, the frequency of HCV core-specific CD4+ cells producing IL-10 was higher in non-SVR than SVR (4.3% vs 1.8%, p=0.05). Comparing patients according to rs12979860 CC vs no CC genotypes, CC genotype patients had more CD56 bright cells (6.6% vs 3.1%, p=0.04), fewer CD3 − CD56 − CD16 + NK cells (8.7% vs 11.1%, p=0.05) and fewer HCV-core specific CD4 + /IL-10 + cells (1.9% vs 4.2%, p=0.05). There were no associations between rs8099917 genotypes TT vs no TT and innate or adaptive immune responses in this cohort. Conclusion: High numbers of CD56 bright NK cells, low numbers of unconventional CD3 − CD56 − CD16 + NK cells, and low HCV-specific IL-10 production at baseline are associated with IL28B gene SNP rs12979860 CC genotype and successful antiviral treatment of CH-C genotype 1. Competing interests: None declared.